TI_GERICHTE 35.2022.35 vom 11. Juli 2022 , Sospensione prestazioni. Ginocchio sinistro. Rinvio per accertamenti (eziologia) - TI Tribunale d'appello (2022)
Sospensione prestazioni. Ginocchio sinistro. Rinvio per accertamenti (eziologia)